1986
DOI: 10.1016/0014-5793(86)80875-4
|View full text |Cite
|
Sign up to set email alerts
|

Control of energy metabolism by glucagon and adrenaline in perfused rat liver

Abstract: Changes in subcellular distribution of adenine nucleotides, mitochondrial/cytosolic proton gradients, rates of respiration, gluconeogenesis (fasted state) and glycogenolysis (fed state) were studied in isolated perfused rat livers following addition of glucagon (IO-@ M) or adrenaline (lo-' M). Glucagon increased the gradient in all states. The cytosolic ATP/ADP ratio was increased in the fasted but decreased in the fed state which is consistent with a diminished futile cycling in gluconeogenesis (fasted state)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 18 publications
0
16
2
1
Order By: Relevance
“…The PMF is composed of membrane potential (ΔΨ m ) and pH gradient (ΔpH m ) components. Although it has not been shown for vasopressin, a number of previous studies have suggested that gluconeogenic hormones such as glucagon, α‐adrenergic agonists and L ‐triiodothyronine increase the PMF in hepatocyte suspensions and perfused liver (Prpic et al ., 1978; Taylor et al ., 1980; Soboll and Scholz, 1986; Halestrap, 1989; Soboll et al ., 1992; Soboll, 1993). However, the measurements of PMF in these studies were carried out in mitochondrial fractions isolated from the cells or tissue subsequent to hormone treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The PMF is composed of membrane potential (ΔΨ m ) and pH gradient (ΔpH m ) components. Although it has not been shown for vasopressin, a number of previous studies have suggested that gluconeogenic hormones such as glucagon, α‐adrenergic agonists and L ‐triiodothyronine increase the PMF in hepatocyte suspensions and perfused liver (Prpic et al ., 1978; Taylor et al ., 1980; Soboll and Scholz, 1986; Halestrap, 1989; Soboll et al ., 1992; Soboll, 1993). However, the measurements of PMF in these studies were carried out in mitochondrial fractions isolated from the cells or tissue subsequent to hormone treatment.…”
Section: Resultsmentioning
confidence: 99%
“…There is, on the other hand, a report showing that the concentration of ornithine in isolated hepatocytes is 1.6 mM in the mitochondrial matrix and 0.6 mM in the cytosol [26]. If these measurements are correct, since the ∆pH across the mitochondrial membrane in perfused liver is about 0.33 unit [27], a concentration gradient of citrulline (in\out) of 5.3 should be sufficient to drive entry of ornithine in exchange for intramitochondrial citrulline. A comparable citrulline gradient is not unlikely to exist in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological significance of APC isoforms is highlighted by the observation that changes in the adenine nucleotide concentration in the mitochondrial matrix, without variation in the whole cell content, occur in many adaptive states. For example, the mitochondrial adenine nucleotide pool has been found to be increased in newborn liver mitochondria 3-4 times within 3-4 h after birth (35) and in adult liver mitochondria upon fasting (50,51), after glucagon treatment (50 -52), and in altered thyroid states (53). On the other hand, it is decreased by hypoxia (54) and ischemia (55), in fast growing hepatomas (56), during hibernation (57), and in copper deficiency (58).…”
Section: Influence Of Membrane Potential and Ph Gradient On The Apc-mmentioning
confidence: 99%